Mass transfer process of petroleum hydrophobic organic compounds from nonaqueous phase into aqueous phase with fungi participation - Ma Xiaokui; Wu Lingling; Lü Tingting; Ding ning; Zhou Lihui; Chen Ling; Wu Zhengchao (浙江大学学报. 农业与生命科学版, 2014)
Due to the high toxicity and low bioavailability, petroleum hydrophobic organic compounds (HOCs) have been found to be deposited in the natural environments and to present danger to human beings. A number of factors may affect the mass transfer of HOCs from nonaqueous phase liquids (NAPLs) into aqueous phase, thus affect their bioavailability and toxicity in aqueous phase.This article reviewed the influence of the fungal species with ability to degrade petroleum HOCs and their physiological activities on the mass transfer of HOCs from NAPLs into aqueous phase, including the influence of fungi on the process of HOCs mass transfer, the metal toxicity changes and the biological effect resulting from mass transferring. This review firstly focused on the effect of fungi participation on the dynamics of mass transfer of the petroleum HOCs to aqueous phase, subsequently analyzed its influence on the metal toxicity and biological effects.Compared to bacteria, fungi can use a variety of petroleum HOCs due to their hydrophobic mycelium networks, specific physiological biochemical and ecological advantages. In addition, fungi possess ecological capacity, dominating the living biomass in soil and being abundant in aqueous systems. These facts suggest that fungus may affect the mass transfer of petroleum HOCs to aqueous phase through its physiological activities. But biological factors affecting on this mass transfer and its mechanism of action are unknown. Fungi possess high ecological capacity participating in the bioremediation process of the polluted organic chemicals. Furthermore, the abilities of these fungi to form extended mycelial networks, the low specificity of their catabolic enzymes and their independence from using pollutants as growth substrate may make them better suited for bioremediation processes especially in the complicated pollution environments and which may affect the mass transfer of petroleum HOCs to aqueous phase.These studies will be important for human beings to understand the effect of biological factors on the bioavailability and biological toxicity of petroleum HOCs and heavy metal pollution in ocean water. They also will be of great significance for us to understand the major environmental problems such as oil spills, and to further address the conversion rule of non-biomass HOCs to biomass in nature.